Pelatihan Guru dalam Pengembangan Modul IPA Berbasis Lingkungan Lokal Berbantuan AI sebagai Upaya Meningkatkan Literasi Sains dan Berpikir Kritis Siswa di SD YPK Ermasu Kota Merauke - Syahfitriani Br Ginting; Herrio Tekdi Nainggolan (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the competencies of teachers at SD YPK Ermasu in developing locally based science modules supported by artificial intelligence (AI) to improve students’ scientific literacy and critical thinking skills. The program was implemented through training and mentoring activities involving 22 teachers. Evaluation instruments included a 20-item multiple-choice test, short interviews, and documentation. Data analysis employed the Gain Score method to identify differences between teachers’ initial and final competencies following the training. The results indicate a Gain Score of 0.56, which falls into the moderate category, demonstrating a positive impact on teachers’ skills in designing locally contextualized science modules using AI. This improvement is evidenced by differences between pre-test and post-test results. In addition, interview findings reveal that teachers felt assisted by the use of AI in developing instructional modules. The teachers also expressed expectations for the continuation of similar programs to further support their understanding and professional development.